In Vitro Release of Anthocyanins from Microencapsulated Natal Plum (Carissa macrocarpa) Phenolic Extract in Alginate/Psyllium Mucilage Beads - Faith Seke; Vimbainashe E. Manhivi; Retha M. Slabbert; Yasmina Sultanbawa; Dharini Sivakumar (Foods, 2022)
Natal plum (Carissa macrocarpa) contains anthocyanins, cyanidin 3-O-β-sambubioside (Cy-3-Sa), and cyanidin 3-O-glucoside (Cy-3-G) that possess great bioactive properties. During in vitro gastrointestinal digestion, Cy-3-Sa and Cy-3-G are highly sensitive to pH changes and have low bioaccessibility rates of 7.9% and 22%, respectively. This study aimed to therefore use microencapsulation techniques to improve the bioaccessibility of Cy-3-Sa and Cy-3-G. The crude anthocyanin-rich extract was extracted from freeze-dried Natal plum fruit using ultrasonic-assisted ethanol extraction. The anthocyanin-rich extract was encapsulated using the ionic gelation method. Four distinct carrier agents, namely sodium alginate, pectin, xanthan gum and psyllium mucilage were used to form the wall materials. Encapsulation efficiency was highest for alginate/psyllium mucilage beads (93.67%), while alginate showed the least efficiency (86.80%). Scanning Electron Microscopy revealed a cracked and porous structure for the Natal plum extract and a continuous smooth structure for all the beads. Fourier transform infrared spectroscopy showed peaks at 3300 and 1610 cm−1, confirming the presence of polyphenols and polysaccharides in all beads. Thermal stability was higher for the alginate/psyllium mucilage beads and the observed thermal transitions were due to the bonds formed between the polymers and the polyphenols. Alginate beads combined with xanthan gum, pectin, and psyllium mucilage showed a prolonged release of anthocyanins compared to alginate in vitro alone. The highest anthocyanin bioaccessibility was obtained from alginate/psyllium mucilage beads (85.42 ± 1.03%). The results showed the effectiveness of alginate/psyllium mucilage beads in improving stability and in vitro anthocyanin release.